UPAYA MENINGKATKAN KESADARAN DAN KREATIVITAS MASYARAKAT MELALUI PEMBUATAN PRODUK KOMPOS DAN ECOBRICK DI DESA BILEBANTE - Brata, Dewa Gede Radya Pito; Sirtufillaeli, Sirtufillaeli; Hidayanti, Devina Permata; Datulmizan, Afrizki Agi; Alfarizi, Muhamad Satriawan; Zahrani, Hanifa; Aulia, Cantika; Lazuardi, Nikita Padmi; Hadiati, Ilmiatun Hadiati; Arnita, Eva; Zubair, Muh (Universitas Mataram, 2024)
Kuliah Kerja Nyata (KKN) in Bilebante Village, Pringgarata Subdistrict, Central Lombok Regency, West Nusa Tenggara, aims to enhance waste management with a focus on creative economy and sustainable tourism. Bilebante Village, inhabited mainly by the productive age group and lacking adequate waste management facilities, faces significant waste issues, particularly the improper disposal of waste into rivers. This KKN program begins with a survey to identify problems and design solutions, followed by socialization about the importance of organic and inorganic waste management. The distribution of trashbags to residents aims to facilitate waste separation, and the controlling phase ensures the implementation of waste management methods through guidance and evaluation. The results show positive community responses, with residents starting to apply waste management practices by producing organic fertilizer and ecobricks. The program is expected to improve environmental cleanliness, advance the tourism village, and foster creative economic development in Bilebante Village.